Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/1535-7163.mct-18-0644
|View full text |Cite
|
Sign up to set email alerts
|

TAS4464, A Highly Potent and Selective Inhibitor of NEDD8-Activating Enzyme, Suppresses Neddylation and Shows Antitumor Activity in Diverse Cancer Models

Abstract: NEDD8-activating enzyme (NAE) is an essential E1 enzyme of the NEDD8 conjugation (neddylation) pathway, which controls cancer cell growth and survival through activation of cullin-RING ubiquitin ligase complexes (CRL). In this study, we describe the preclinical profile of a novel, highly potent, and selective NAE inhibitor, TAS4464. TAS4464 selectively inhibited NAE relative to the other E1s UAE and SAE. TAS4464 treatment inhibited cullin neddylation and subsequently induced the accumulation of CRL substrates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…We have reported that TAS4464 inhibits the neddylation pathway via inhibition of NAE, which leads to accumulation of CRL substrates in several solid and hematologic tumor cell lines . In the present study, TAS4464 also reduced the levels of neddylated UBC12 (an E2 for NEDD8) and neddylated cullin1 (a component of CRL) and selectively induced the accumulation of the CRL substrates p‐IκBα, CDT1, NRF2 and p21, but not substrates of non–CRL E3s (GADD34 and PTTG), in MM.1S cells in a dose‐dependent and time‐dependent manner (Figure ).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…We have reported that TAS4464 inhibits the neddylation pathway via inhibition of NAE, which leads to accumulation of CRL substrates in several solid and hematologic tumor cell lines . In the present study, TAS4464 also reduced the levels of neddylated UBC12 (an E2 for NEDD8) and neddylated cullin1 (a component of CRL) and selectively induced the accumulation of the CRL substrates p‐IκBα, CDT1, NRF2 and p21, but not substrates of non–CRL E3s (GADD34 and PTTG), in MM.1S cells in a dose‐dependent and time‐dependent manner (Figure ).…”
Section: Resultssupporting
confidence: 61%
“…TAS4464 is one of the most selective and potent NAE inhibitors reported to date both in vitro and in vivo . TAS4464 exhibits widespread antiproliferative activity in various tumor cell lines and is especially active against most hematologic malignancy cell lines, including myeloma‐derived cell lines …”
Section: Introductionmentioning
confidence: 99%
“…The interaction of CDT1 with geminin also serves to prevent re-replication during normal mitotic growth 12,15,17,45,47 . Interfering with the degradation and inactivation of CDT1, either by geminin depletion 47 or by inhibiting the activity of cullinanchored ubiquitin ligases 28,31,33,46 , can be exploited to trigger re-initiation and subsequent selective killing of cancer cells. We observed that cancer cells that undergo partial genome duplication due to the persistence of pre-RCs on chromatin exhibit similar DNA synthesis characteristics regardless of the mechanisms that prevent pre-RC dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…However, excess initiation of DNA replication can have deleterious consequences, including oncogenic transformation of normal cells and increased genomic instability in cancer 28,44,45,47 , consistent with our observations suggesting that massive overreplication can lead to senescence. Those consequences can be exploited therapeutically to induce selective killing of cancer cells 28,[31][32][33]47 . The results reported here imply that circumventing the strong inhibitory interactions that normally prevent excess DNA synthesis can occur via at least two pathways, each activating a distinct set of replication origins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation